The impact of the use of video-based educational interventions on patient outcomes in hospital settings: A scoping review. Issue 12 (December 2018) - Dahodwala, Murtaza; Geransar, Rose; Babion, Julie; de Grood, Jill; Sargious, Peter
Highlights: A scoping review of video-based patient education in hospitalized patients was conducted. Many studies show positive effects of video-based education compared to standard interventions. Video-based patient education is effective for improving short-term health literacy goals. More research is needed to assess impact on long term behavior or lifestyle modifications. Combining educational methods over an extended period may support longer-term health outcomes. Abstract: Objective: To summarize the literature on the impact of video-based educational interventions on patient outcomes in inpatient settings as compared to standard education techniques. Methods: This review followed a scoping review methodology. English language articles were searched in Pubmed, Medline, Cochrane, and CINAHL databases. Inclusion criteria were: use of video-based educational interventions, and inpatient hospital settings. Abstracts were reviewed and selected according to predetermined criteria, followed by full-text scrutiny. Results: Sixty-two empirical studies were identified, with 38 (61%) reporting a significant positive effect of video-based educational interventions on patient outcomes, compared to control groups (i.e., standard education). Three different types of video-based educational intervention formats were identified: animated presentations, professionals in practice, and patient narratives. Outcome types included: knowledge-based, clinical, emotional, and behavioral, with knowledge-based most prevalent. Conclusion: Video-based educational interventions are common in the hospital setting. These interventions are effective at improving short-term health literacy goals, but their impact on behavior or lifestyle modifications is unclear. Their effectiveness also depends on presentation format, timing, and the patient's emotional well-being. Practice implications: Video-based educational delivery is effective for improving short-term health literacy, however a combination of approaches delivered over an extended period of time may support improving longer-term health outcomes.